The Spiekeroog Coastal Observatory: A Scientific Infrastructure at the Land-Sea Transition Zone (Southern North Sea) - Zielinski, Oliver; Pieck, Daniela; Schulz, Jan; Thölen, Claudia; Wollschläger, Jochen; Albinus, Michelle; Badewien, Thomas H.; Braun, Axel; Engelen, Bert; Feenders, Christoph; Fock, Swaantje; Lehners, Carola; et al. (Frontiers in Marine Science, 2022)
Coastal observatories are key to improve the understanding of processes within the coastal area and their interactions with regional and global environmental changes. The land-sea transition zone is an essential area that allows research on unique scientific questions under anthropogenic and natural influences. Amid the Wadden Sea UNESCO world natural heritage site – the largest tidal flat region worldwide – the barrier island Spiekeroog is an excellent location for an observatory studying land-sea interactions. The integrated Spiekeroog Coastal Observatory (SCO) operated by the Institute for Chemistry and Biology of the Marine Environment (ICBM, University of Oldenburg) is dedicated to interdisciplinary marine and terrestrial ecosystem research. Its position within the tidal area and the multitude of research-field addressed establishes the SCO as a unique coastal observatory with the potential to identify patterns in long-term variability and simultaneously understanding short-term changes. The establishment of the Time-Series Station (TSS) Spiekeroog in a tidal channel west of Spiekeroog back in 2002 laid the foundation of the SCO. Since then, the observatory is expanding continuously and is now representing a valuable asset supporting education, industry, government, and environmental conservation efforts in the area. Summing up the infrastructure and technical components, the importance of the SCO is evident, and individual projects greatly benefit from the collaboration with the partners in and the elements of the SCO. Harmonizing the infrastructure and competences of contributing partners will be a next step to further consolidate the SCO. A challenge poses the maintenance of the SCO based on projects, which is focused on the addition of new facilities, not maintaining, refurbishing, or (if necessary) deconstructing existing infrastructure. Therefore, structural support and funding opportunities not linked to projects but aiming to sustain observational capacities are required.